ISLAM DAN BUDAYA LOKAL: ANALISIS METODOLOGIS TERHADAP TRADISI KEAGAMAAN MASYARAKAT JAWA - Ramadhina Qurrota Ayun; Shiva Amiliya Aidah; Nurul Ilma Aulia; Nabila Hasna Utama; Nanang Hasan Susanto (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This article aims to examine the reciprocal relationship between Islam and local culture in the religious practices of Javanese society through a literature review method. The study reviews various scholarly works and recent field research (2020–2025) that discuss traditions such as slametan, nyadran, tingkeban, sedekah bumi, as well as the pesantren education model based on kitab kuning (classical Islamic texts) as forms of integration between Islam and Javanese culture. The analysis employs an interpretive approach to explore the symbolic meanings and social functions of these traditions. The findings indicate that the development of Islam in Java is accommodative, adaptive, and contextual. Local religious traditions are not viewed as contradictory to Islamic teachings but rather serve as means of da’wah (religious outreach), moral education, and the strengthening of religious moderation. Therefore, methodological approaches in Islamic studies should consider local culture as an integral part of the epistemology of Islam Nusantara